(untitled) (Research, Society and Development, 2022)
The objective of this work was to analyze the hematological parameters of patients positive for COVID-19, admitted to the COVID intensive care unit (ICU-COVID) of the University Hospital Lauro Wanderley (HULW), to correlate these data with the clinical conditions of critically ill patients, compared to patients in the ward of the COVID Infectious Parasitic Diseases Unit (IDP -COVID). The study population consisted of patients in (ICU-COVID) and (IDP-COVID) of both genders, considering children, adolescents, adults, and elderly people hospitalized in this unit with positive serology or molecular tests (RT-PCR). This was a retrospective observational cross-sectional study involving patients in the (ICU-COVID) and (IDP -COVID) of the HULW. The study was carried out in accordance with the requirements of the Research Ethics Committee (CAAE 46718921.4.0000.5183) of the HULW. 152 exams were analyzed. Of these, 88 (58%) were male and the average in relation to the age group was 61.5 years. By correlating the data obtained from inpatients in the COVID-ICU and IDP-COVID, it can be observed in the ICU-COVID patients there was the predominance of leukocytosis (50.4%), as well as lymphopenia (90.9%), neutrophilia (80%) and anemia (70%). Thrombocytopenia is present in 23% of patients in the COVID-ICU and alterations in Prothrombin Time (PT) and Activated Partial Thromboplastin Time (APTT) were identified. These data corroborate the literature, in which the total leukocyte count varies between patients, which may reflect the dominance of lymphopenia or neutrophilia. Taken together, decreased lymphocytes accompanied by mild thrombocytopenia are among the most common abnormal findings that attract attention in the blood count of COVID-19 patients.